2016
DOI: 10.1039/c6ra11869k
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional macroporous CNT–SnO2 composite monolith for electricity generation and energy storage in microbial fuel cells

Abstract: A facile electrophoretic deposition method was used to prepare three-dimensional macroporous CNT-SnO 2 monolith as the MFC anode. This 3D CNT-SnO 2 composite presents a clear micro-structure of CNT inside and amorphous SnO 2 nanoparticles coating around the CNT surface, and has an integration of electricity generation and energy storage in MFCs. Experimental results show that CNT-SnO 2 composite possesses good biocompatibility and improved electrical conductivity. Compared with CNT, CNT-SnO 2 presents a much h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The weight ratio of Sn and C was approximately 0.76 which indicated some loss of carbon may be due to heat treatment. Also the atomic ratio of O to Sn was found to be 1.26 indicating a high number of oxygen vacancies in the synthesized sample 43 . A comparative study of the morphologies of the SnO 2 -CNT nanohybrids with recent reports has been summarized in Table S1 (ESI).…”
Section: Resultsmentioning
confidence: 92%
“…The weight ratio of Sn and C was approximately 0.76 which indicated some loss of carbon may be due to heat treatment. Also the atomic ratio of O to Sn was found to be 1.26 indicating a high number of oxygen vacancies in the synthesized sample 43 . A comparative study of the morphologies of the SnO 2 -CNT nanohybrids with recent reports has been summarized in Table S1 (ESI).…”
Section: Resultsmentioning
confidence: 92%
“…Hybrid nanomaterials can function as novel electrode materials, signal amplifiers, and catalysts of the electrochemical reaction of the product generated in situ during the biorecognition event. To date, the most common hybrid nanomaterials applicable to electrochemical biosensing include metallic nanostructures [27,28], silicon nanomaterials [29][30][31][32], carbon nanostructures [17,33,34], and semiconductor polymers [35][36][37][38][39], with great potential for the development of electrochemical nanobiosensors with enhanced performance [40][41][42], as commented. This section will comment on the main examples of the last ten years (Table 1), focused on nanostructured nanomaterials employed in developing nanohybrids for their implementation in electrochemical biosensing.…”
Section: Nanohybrids and Nanocompositesmentioning
confidence: 99%
“…It has been reported that the construction of modified electrodes with hybrid or nanocomposite materials based on carbon nanomaterials doped with metallic nanoparticles [27,28,[152][153][154] and semiconductor polymers [35][36][37][38][39] has great potential for the development of biosensors with enhanced performance (Table 3). For example, an immunosensor based on cadmium selenide (CdSe)-QD-melamine has been explored to detect CEA.…”
Section: Examples Of Nanobioengineered Platforms For Electrochemical ...mentioning
confidence: 99%
“…[ 142 ] Tin oxide has also been widely applied as electrode modifier owing to its distinguished physicochemical characteristics, excellent conductivity, great abundance, easy availability and relatively low cost. [ 143 ] Iron oxides, including Fe 2 O 3 , Fe 3 O 4 , FeO(OH), etc., have been applied as electrode additives to enhance EET efficiency. [ 144 ] Besides, carbon cloth was modified by doping nanostructured NiO, and the nanocomposite anode achieved three times greater power output in comparison with untreated anode owing to the larger accessible active sites, the greater biomass and the increased EET rate.…”
Section: Development Of Anode Materialsmentioning
confidence: 99%